تقويم أسئلة امتحانات اللغة العربية للشهادة الدينية العالية الماليزية في ضوء مستويات بلوم المعرفية : دراسة وصفية تحليلية - Abdul Ghofour bin Ruslan (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
This study aims to identify and analyze the levels of questions available in the Arabic examination for the Sijil Tinggi Agama Malaysia (STAM) during the academic year 2013, 2014, and 2015 according to Bloom's taxonomy of cognitive domains (remembering, understanding, applying, analyzing, evaluating, and creating). To achieve the purpose of this study, the researcher used content analysis approach as an analysis unit to analyze the questions. The total number of questions were 710. The results indicate that Arabic examination questions for the Sijil Tinggi Agama Malaysia in the years referred to in this study focused on the lower-order thinking skills (remembering 40%, understanding 35%, applying 12%). On the other hand, analyzing occurred in higher-order thinking skills (12%), while the other two levels, evaluating and creating received poor attention at 0% and 1%, respectively.